Analisis Kebijakan Fiskal Terhadap Pertumbuhan Ekonomi Di Indonesia Tahun 2024 - Hasibuan, Usni Majida; Lubis, Wina Adelia; Angrilla, Tengku Della; Nasution, Yenni Samri Juliati (WELFARE: Journal of Islamic Economics and Finance, 2025)
This study aims to analyze the impact of Fiscal policy on Indonesia's economic growth in 2024. The data used comes from the official publication of the Ministry of Finance and Central Statistics. The research method includes analysis of historical data and economic forecasts, as well as the use of macroeconomic models to measure the effects of different tax policies. The data used comes from official sources such as the Central Bureau of Statistics (BPS) and Bank Indonesia (BI), as well as state transactions. Effective and sustainable fiscal policy is needed to support stable and sustainable economic growth in Indonesia. This report is expected to  be a reference for political  decisions  in  the language of optimal financial strategies to support Indonesia's economic growth.